Factors for Prospective Grooms Committing Identity Falsification in Marriage in Boliyohuto Sub-District - Pakaya, Siti Nuraisyah; Kasim, Nur Mohamad; Nanang Meiske Kamba, Sri (Estudiante Law Journal, 2024)
The purpose of conducting this research is to find out what factors are the reasons for the prospective groom to falsify his identity in marriage in Boliyohuto District. The research method used in this article is to use empirical research methods by taking a qualitative approach. The results of this study show that in the case of a marriage annulment lawsuit at the Gorontalo Religious Court, there was one party who filed for annulment of her marriage on the grounds that her husband had falsified his identity so that she felt she had been lied to, claiming to be a virgin. After a week of having relations as husband and wife, the wife found out that her husband already had a wife and child so she sued for annulment of the marriage. As a result of the annulment of marriage that occurred in the case under study, the wife felt disadvantaged, which in law violates Article 27 paragraph (2) of Law Number 1 of 1974 concerning Marriage which reads: "A husband or wife may file a petition for annulment of marriage if at the time of marriage there is a misconception about the husband or wife".